Use of bismut subgalate as a hemostatic agent and its influence on tissue repair in dental surgerys (Research, Society and Development, 2021)
During dental surgical procedures, there is a risk of bleeding episodes that may be associated with local and / or systemic factors. The bismuth subgalate (BS) may be used as a local hemostatic. The aim of this study was to evaluate the use of BS in dental surgery, addressing its effectiveness as a hemostatic substance. For the literature review, articles were searched in the SciELO, PubMed and Scopus databases. Pre-clinical and clinical articles that discuss BS influence in dental surgeries were selected. BS is a heavy metal and insoluble in water and can be used orally or topically. It has effectiveness in hemostasis of palatal donor areas, in dental extraction surgeries and even in dialysis patients. Studies carried out in humans and animals have shown deleterious effects on tissue repair using BS. Despite its effectiveness as a hemostatic agent, it can cause changes in tissue repair, limiting its use to specific cases in order to avoid risks of trans or postoperative hemorrhage. Therefore, although the literature demonstrates advantages in the use of BS as a hemostatic agent, there are not many clinical studies. Further research is needed in order to analyze the clinical efficiency on tissue repair.